ENGARUH RELIGIUSITAS, KEPERCAYAAN, CITRA PERUSAHAAN, DAN SISTEM BAGI HASIL TERHADAP MINAT NASABAH MENABUNG DAN LOYALITAS DI BANK SYARIAH MANDIRI (Studi Kasus Pada Nasabah Bank Syariah Mandiri Gresik - Nurul Khotimah (Universitas 17 Agustus 1945 Surabaya, 2018)
his research aims to examine and analyze the influence of religiosity, trust, corporateimage, and profit sharing system towards customer saving interest and customer loyalty inBank Syariah Mandiri. This research is a quantitative research with descriptive approach.The population in this research is the customer who opened a savings account at BankSyariah Mandiri Branch Gresik. The sample was taken by accidental sampling techniquewith criterion as customer opening a savings account at Bank Syariah Mandiri BranchGresik, and has 17 - 50 years old as many as 115 respondent. Analyze data used PLS withWarpPLS 5.0 program. The results of this study indicate that partially Religiosity, Trust, andProfit Sharing System, have a positive and significant effect on the customer's interest insaving, but the company's image has unsignificant effect on the customer saving interest,while Religiosity, Trust has a positive and significant effect on customer loyalty, but companyimage and profit sharing system have a unsignificant effect on customer loyalty, the otherhand state that customer saving interest has a positive and unsignificant effect on customerloyalty.Keywords : Religiosity, Trust, Corporate Image, Profit Sharing System, Customer SavingInterest, and Customer Loyalty.